Banks and the capital market: an Australian study - Perkins, J. O. N.; Sullivan, J. E. ([Carlton, Vic.] Melbourne University Press, 1970)
The study is intended to acquaint students, schools and the general readers with the working of the Australian banking system in the context of the capital market.
suggestion and further reading
includes bibliographical index
asm; 12/02/19
Loans
Keywords: Capital market; Financial institutions; Banks and banking